SpyDisplay: A versatile phage display selection system using SpyTag/SpyCatcher technology. Issue 1 (31st December 2023) - Kellmann, Sarah-Jane; Hentrich, Christian; Putyrski, Mateusz; Hanuschka, Hanh; Cavada, Manuel; Knappik, Achim; Ylera, Francisco
ABSTRACT: Phage display is an established method for the in vitro selection of recombinant antibodies and other proteins or peptides from gene libraries. Here we describe SpyDisplay, a phage display method in which the display is achieved via SpyTag/SpyCatcher protein ligation instead of genetically fusing the displayed protein to a phage coat protein. In our implementation, SpyTagged antibody antigen-binding fragments (Fabs) are displayed via protein ligation on filamentous phages carrying SpyCatcher fused to the pIII coat protein. A library of genes encoding Fab antibodies was cloned in an expression vector containing an f1 replication origin, and SpyCatcher-pIII was separately expressed from a genomic locus in engineered E. coli . We demonstrate the functional, covalent display of Fab on phage, and rapidly isolate specific high-affinity clones via phage panning, confirming the robustness of this selection system. SpyTagged Fabs, the direct outcome of the panning campaign, are compatible with modular antibody assembly using prefabricated SpyCatcher modules and can be directly tested in diverse assays. Furthermore, SpyDisplay streamlines additional applications that have traditionally been challenging for phage display: we show that it can be applied to N-terminal display of the protein of interest and it enables display of cytoplasmically folding proteins exported to periplasm via the TAT pathway.